Intratumoural interleukin 12 gene therapy stimulates the immune system and decreases angiogenesis in dogs with spontaneous cancer. (9th August 2016) - Cicchelero, L.; Denies, S.; Haers, H.; Vanderperren, K.; Stock, E.; Van Brantegem, L.; de Rooster, H.; Sanders, N. N.
Abstract: Interleukin 12 (IL‐12) is a powerful immunostimulatory cytokine with a strong antitumoural activity. In this work, the immunological, anti‐angiogenic and clinical effects of three consecutive intratumoural IL‐12 electrogene therapy (EGT) treatments were evaluated in nine dogs with spontaneous cancer. In all the dogs, tumour biopsies and blood samples were taken prior, during and after the intratumoural IL‐12 EGT (on days 1, 8, 35 and 1, 3, 8, 15, 35, respectively). An initial decrease in immune cells was followed by an increase above baseline 1–3 weeks after treatment initiation. Interestingly, the decrease in peripheral leukocytes 2 days after the first intratumoural IL‐12 EGT coincided with erythema and tumour swelling. Transient increases of IL‐12 and interferon γ were measured in the serum and the tumour tissue, whereas IL‐10 transiently increased only in the serum. The effect of intratumoural IL‐12 EGT on the levels of IL‐24 and vascular endothelial growth factor in the sera and tumour biopsies differed per dog. Via contrast‐enhanced ultrasound (US) (on days 1, 8 and 35), we demonstrated that intratumoural IL‐12 EGT resulted in a significant decrease of the relative blood volume and blood flow speed in the tumour compared with baseline. Metastases were present in two dogs. In one of these dogs, IL‐12 EGT of the primary tumour caused a transient partial regression of the metastases, but not of the primary tumour. The second dog with metastases did not survive long enough to complete the entire treatment cycle. Despite encouraging immunostimulatory and anti‐angiogenic effects after intratumoural IL‐12 EGT, no clinically relevant outcomes were observed in this study, as persistent tumour regression could not be obtained. On the other hand, the laboratory and US results hold great promise for combinatorial strategies of intratumoural IL‐12 EGT with conventional antitumour (immuno)therapies.